The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10661-006-9442-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Inter-Annual Variations in Methyl Mercury Concentrations in Zooplankton from Boreal Lakes Impacted by Deforestation or Natural Forest Fires

Abstract: We compared the effects of natural and anthropogenic watershed disturbances on methyl mercury (MeHg) concentration in bulk zooplankton from boreal Shield lakes. MeHg in zooplankton was monitored for three years in nine lakes impacted by deforestation, in nine lakes impacted by wildfire, and in twenty lakes with undisturbed catchments. Lakes were sampled during spring, mid- and late summer. MeHg in zooplankton showed a seasonal trend: concentrations were the lowest in spring, then peaked in mid-summer and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 42 publications
2
26
0
1
Order By: Relevance
“…Steedman et al (1998) suggest that removing riparian forest, the thermal regime of the lentic environments can be modified, affecting mainly the littoral zones of shallow lakes. In another study, Garcia et al (2007) found increases in the MeHg (Metyl Mercury) concentrations at zooplankton's tissues in boreal lakes impacted by deforestation. Deforestation impacts are well known and reported for the lotic environments, which are affected mainly by reduction of the littoral complexity and a high input of land sediments.…”
Section: Discussionmentioning
confidence: 95%
“…Steedman et al (1998) suggest that removing riparian forest, the thermal regime of the lentic environments can be modified, affecting mainly the littoral zones of shallow lakes. In another study, Garcia et al (2007) found increases in the MeHg (Metyl Mercury) concentrations at zooplankton's tissues in boreal lakes impacted by deforestation. Deforestation impacts are well known and reported for the lotic environments, which are affected mainly by reduction of the littoral complexity and a high input of land sediments.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the sediments from erosion, Steedman and France (2000) found that wind-blown sediment from black sprucejack pine clearcuts, roads, and skid trails, where soil disturbance is large and able to reach the lake, may have led to elevated levels of littoral sedimentation, although it was thought this mechanism would not cause important changes in water quality. Although some studies do not examine sedimentation directly, many have found that water clarity is reduced by timber harvesting over a variable range in time (one to four years) following harvest France et al 2000;Steedman 2000;Steedman and Kushneriuk 2000;Knapp et al 2003;Garcia et al 2007;Bertolo and Magnan 2007;Winkler et al 2009) although one study found no effect on water clarity (Prepas et al 2001a). …”
Section: Suspended Sedimentsmentioning
confidence: 99%
“…A rise in groundwater level following timber harvesting can mobilize DOC both during peak and base flow conditions (Laudon et al 2009). Most studies reviewed found an increase in surface water DOC concentrations following harvest that were maintained for a few years followed by a decline towards pre-harvest conditions in lakes France et al 2000;Garcia et al 2007;Lamontagne et al 2000;Steedman 2000;Bertolo and Magnan 2007;Hausmann and Pienitz 2009;Winkler et al 2009). A few studies reviewed showed no effect in streams (Hillman et al 1997) or lakes (Knapp et al 2003;Desrosiers et al 2006), and one study showed a negative effect in lakes (France et al 1996) of harvesting on surface water DOC concentrations.…”
Section: Dissolved Organic Carbon and Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in this study, MeHg was only determined early in the summer and we made assumptions that this concentration was the same throughout the summer. Garcia et al (2007) showed that in boreal lakes some seasonal variation can occur and MeHg concentration can increase by 48% from May to July and then decrease nearly to the same level observed in May at the end of summer. The sensitivity of this parameter probably represents the main disadvantage of the Hg mass balance model (Trudel et al 2000) and may be the less reliable parameter in this study.…”
Section: Leuciscus Leuciscus Rutilus Rutilus Abramis Abrama and Almentioning
confidence: 88%